Visualizing cancer-originating acetate uptake through monocarboxylate transporter 1 in reactive astrocytes in the glioblastoma tumor microenvironment - Kim, Dongwoo; Ko, Hae Young; Chung, Jee-In; Park, Yongmin Mason; Lee, Sangwon; Kim, Seon Yoo; Kim, Jisu; Chun, Joong-Hyun; Han, Kyung-Seok; Lee, Misu; Ju, Yeon Ha; Park, Sun Jun; et al. (Duke University Press, 2024)
Background Reactive astrogliosis is a hallmark of various brain pathologies, including neurodegenerative diseases and glioblastomas. However, the specific intermediate metabolites contributing to reactive astrogliosis remain unknown. This study investigated how glioblastomas induce reactive astrogliosis in the neighboring microenvironment and explore 11C-acetate PET as an imaging technique for detecting reactive astrogliosis. Methods Through in vitro, mouse models, and human tissue experiments, we examined the association between elevated 11C-acetate uptake and reactive astrogliosis in gliomas. We explored acetate from glioblastoma cells, which triggers reactive astrogliosis in neighboring astrocytes by upregulating MAO-B and monocarboxylate transporter 1 (MCT1) expression. We evaluated the presence of cancer stem cells in the reactive astrogliosis region of glioblastomas and assessed the correlation between the volume of 11C-acetate uptake beyond MRI and prognosis. Results Elevated 11C-acetate uptake is associated with reactive astrogliosis and astrocytic MCT1 in the periphery of glioblastomas in human tissues and mouse models. Glioblastoma cells exhibit increased acetate production as a result of glucose metabolism, with subsequent secretion of acetate. Acetate derived from glioblastoma cells induces reactive astrogliosis in neighboring astrocytes by increasing the expression of MAO-B and MCT1. We found cancer stem cells within the reactive astrogliosis at the tumor periphery. Consequently, a larger volume of 11C-acetate uptake beyond contrast-enhanced MRI was associated with a worse prognosis. Conclusions Our results highlight the role of acetate derived from glioblastoma cells in inducing reactive astrogliosis and underscore the potential value of 11C-acetate PET as an imaging technique for detecting reactive astrogliosis, offering important implications for the diagnosis and treatment of glioblastomas.